Cultural influences on creativity and academic achievement - Palaniappan, Ananda Kumar; Md Nor, Mariani; Subramaniam, S.R. (2008)
It has been found that high achievers tend to be very academically oriented either due to home or school environment or the education system that tends to encourage rote learning and convergent thinking. At the same time, these same factors has been found to stifle their creative thinking abilities. Hence, students who are high academic performers tend to be less creative than low academic performers and this is especially true with students in higher end of the intelligence continuum.In the 1990's several initiatives had been taken to revamp the Malaysian curriculum and teaching to enhance the thinking skills and creativity among elementary and secondary school students. Since then no studies have been undertaken to investigate whether changes have occurred in the relationships between creativity and academic achievement and how this relationships vary in the intelligence continuum. Cultural influences have been found to influence the development of creativity and academic performance (Palaniaapan, 1994; Yong, 1986). Since the culture of the western countries such as United States is quite different from that of Malaysia especially in the teaching and learning context, it would also be beneficial to investigate whether any cultural differences exist in the nature of these relationships and the possible existence of the intelligence thresholds.